Correcting Misperceptions about the MMR Vaccine: Using Psychological Risk Factors to Inform Targeted Communication Strategies. (June 2021) - Lunz Trujillo, Kristin; Motta, Matthew; Callaghan, Timothy; Sylvester, Steven
Many Americans endorse misinformation about vaccine safety. This is problematic because those who do are more likely to resist evidence-based policies, such as mandatory vaccination for school attendance. Although many have attempted to correct misinformation about vaccines, few attempts have been successful. This study uses psychological correlates of vaccine misinformation acceptance to develop a novel misinformation correction strategy by tailoring provaccine messages to appeal to these psychological traits. For example, people with higher moral purity levels are more likely to view vaccines as contaminating the body, but messages highlighting disease via under-vaccination can use their higher moral purity to push them toward vaccine support. Using a large survey experiment ( N = 7, 019) and a smaller replication experiment ( N = 825) of American adults, we demonstrate that interventions designed to appeal to people high in moral purity and needle sensitivity—two relatively understudied correlates of vaccine misinformation support—can also be targeted to effectively reduce vaccine misinformation endorsement. This study provides a better understanding of the psychological origins of misinformed political and policy attitudes, and it suggests a strategy for combating policy-related misinformation more generally, ultimately boosting support for evidence-based policies.